2021
DOI: 10.3390/ijerph182010645
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationship between Korean Adolescent’s Sports Participation, Optimism, Pessimism, Self-Regulation, and Coronavirus-Related Stress in the Pandemic Situation

Abstract: This study aimed to examine the relationships between sports participation, optimism/pessimism, self-regulation, and coronavirus-related stress in Korean adolescents during the pandemic situation. Specifically, we attempted to offer valuable information that could help to alleviate coronavirus-related stress in adolescents by promoting participation in sports and the development of optimism and self-regulation. To achieve this aim, we conducted an online survey of 836 Korean adolescents in the pilot and main s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…Mothers who believed that VL of their children had a negative impact on their life reported higher stress levels than those who did not report such an impact. This is consistent with the study by Song et al who implied in their study on adolescents in Korea the negative impacts pessimism has on increased COVID-19-related stress, while, on the other hand, optimism showed a decreased level of stress [ 17 ]. Moreover, Arslan et al studied the effects of pessimism and optimism on COVID-19-related stress in Turkish adults.…”
Section: Discussionsupporting
confidence: 92%
“…Mothers who believed that VL of their children had a negative impact on their life reported higher stress levels than those who did not report such an impact. This is consistent with the study by Song et al who implied in their study on adolescents in Korea the negative impacts pessimism has on increased COVID-19-related stress, while, on the other hand, optimism showed a decreased level of stress [ 17 ]. Moreover, Arslan et al studied the effects of pessimism and optimism on COVID-19-related stress in Turkish adults.…”
Section: Discussionsupporting
confidence: 92%
“…4/7 (57.1%) − 1/1 (100%) Insomnia [ 61 ] b , [ 77 ] b , [ 95 ] ab , [ 103 ] bc [ 72 ] bc , [ 113 ] b − – 4/6 (66.7%) − 1/1 (100%) − – 4/6 (66.7%) ? 1/2 (50%) COVID-19 Stress [ 73 ] bc , [ 93 ] b [ 65 ] b − 2/3 (66.7%) − 2/3 (66.7%) − 1/1 (100%) Fatigue [ 70 ] b , [ 101 ] bc , [ 105 ] ab − – 3/3 (100%) − 1/1 (100%) − – 3/3 (100%) − 1/1 (100%) Mental health problems [ 75 ] a , [ 76 ] abd , [ 96 ] ab − – 3/3 (100%) − – 3/3 (100%) − 2/2 (100%) − 1/1 (100%) Negative affect [ 69 ] b , [ 110 ] bd ...…”
Section: Resultsmentioning
confidence: 99%
“… Song and Lee (2021) and Petruzzello et al (1991) have demonstrated that college students who approach things optimistically frequently engage in sports activities. When college students adopt positive coping, it tends to induce more positive psychological experiences.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%